Verhütung auf Um-Wegen: Vom kumber und der ausbleibenden sach in den (Reise-) Tagezetteln Johanna Thereesias von Harrach, 1676, Madrid – Wien - Fischer-Monzón, Hannah (Avisos de Viena, 2020)
In September 1676, Countess Johanna Theresia von Harrach embarked on a challenging journey from Madrid to Vienna with her five children, while her husband, the imperial ambassador, remained in Madrid. Chronicling her experiences in detailed "Tagzetteln," she recounts the hardships of the journey, including unreliable transportation and health challenges such as smallpox. An unexpected event occurs: Johanna Theresia's menstruation ceases. In one of her notes, she humorously informs her husband of this absence and playfully alludes to potential rumors arising from her unusual travel companions. Despite her apparent lightheartedness, her writings reveal an awareness of societal norms and expectations regarding intimacy and reproductive health. Analyzing these notes provides insights into the personal lives and cultural norms of the 17th century, as well as individual experiences and strategies for coping with travel and reproductive health issues in the Early Modern period.